Preparation of Co3O4/Carbon Derived from Ionic Liquid and Its Application in Lithium-ion Batteries. (10th December 2017) - Wang, Gongrui; Zhu, Fuliang; Xia, Jun; Wang, Lei; Meng, Yanshuang; Zhang, Yue
Abstract: In this paper, we report an ionic liquid derived Co3 O4 /Carbon (Co3 O4 /C) material synthesized by a carbothermic reduction followed by a low-temperature oxidation, which is certified by XRD and TEM. The as-synthesized Co3 O4 /C composite has a uniform structure with well-crystalized Co3 O4 embedded in carbon matrix (onion-like carbon materials). The carbon held tightly on the Co3 O4 particles can prevent the disintegration of Co3 O4 /C composite during cycling and, therefore, improve the integrity of the composite. Moreover, the carbon component of the composite can enhance the dynamic characteristic of the Co3 O4 /C composite, which can accelerate the electronic conductivity. The composite delivers excellent lithium storage performances with outstanding cycling performance (868 and 877 mAh g −1 after 200 cycles at a current density of 89 mAh g −1 ) and admirable rate capability (660 and 669 mAh g −1 at a rate of 2C) in lithium-ion batteries (LIBs), showing great prospect as electrode material for LIBs.